Niger : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2003)
The first progress report of the government of Niger on the implementation of the Poverty Reduction Strategy Paper (PRSP) covers the period January 2002 to June 2003. The implementation of the PRSP has been broadly satisfactory since January 2002, and the report provides a candid review of developments in this regard. The report emphasizes the participatory approach and activities that have been used to reinforce the ownership of the strategy by the population. Real GDP grew at an average annual rate of 5.0 percent in 2001-02.